62.2k views
0 votes
Can someone please solve this for me and explain the steps? Thank you.

Can someone please solve this for me and explain the steps? Thank you.-example-1
User Brandogs
by
6.4k points

1 Answer

3 votes
Answer:

-22

Steps:

Substitute 3 in for x in f(x);

f(3) = 3 - 1

f(3) = 2

Substitute 3 in for x in g(x);

g(3) = 3^2 - 5 * 3

g(3) = 9 - 15

g(3) = -6

Then multiply this by 4;

4g(3) = 4 * -6

4g(3) = -24

Then add these together;

2 + (-24) = -22
User Calfater
by
5.9k points